Functional PPO2 mutations: co‐occurrence in one plant or the same ppo2 allele of herbicide‐resistant Amaranthus palmeri in the US mid‐south. Issue 2 (28th October 2020) - Noguera, Matheus M; Rangani, Gulab; Heiser, James; Bararpour, Taghi; Steckel, Lawrence E; Betz, Michael; Porri, Aimone; Lerchl, Jens; Zimmermann, Sophie; Nichols, Robert L; Roma‐Burgos, Nilda
Abstract: BACKGROUND: Protoporphyrinogen IX oxidase 2 (PPO2) inhibitors are important for the management of glyphosate‐ and acetolactate synthase‐resistant Palmer amaranth [ Amaranthus palmeri (S.) Wats.]. The evolving resistance to PPO inhibitors is of great concern. We surveyed the evolution of resistance to fomesafen in the US Mid‐south and determined its correlation with the known functional PPO2 target‐site mutations (TSM). RESULTS: The 167 accessions analyzed were grouped into five categories, four resistant (147) and one susceptible (20). Arkansas accessions constituted 100% of the susceptible group while the Missouri accessions comprised 60% of the most resistant category. The majority of Mississippi accessions (88%) clustered in the high‐survival‐high‐injury category, manifesting an early‐stage resistance evolution. One hundred and fifteen accessions were genotyped for four known TSMs; 74% of accessions carried at least one TSM. The most common single TSM was ΔG210 (18% of accessions) and the predominant double mutation was ΔG210 + G399A (17%). Other mutations are likely less favorable, hence are rare. All TSMs were detected in three accessions. Further examination revealed that 9 and two individuals carried G399A + G210 and G399A + R128G TSM in the same allele, respectively. The existence of these combinations is supported by molecular modeling. CONCLUSIONS: Resistance to PPO inhibitors is widespread across the Mid‐southern USA. Highly resistant field populations have plants with multiple mutations. G399A is the most prone to co‐occur with other ppo2 mutations in the same allele. Mutation at R128 in the configuration of the PPO2 catalytic domain restrains the co‐occurrence of R128G with ΔG210, making ΔG210 + G399A the most plausible, tolerable functional mutation combination to co‐occur in the same ppo2 allele. Abstract : Amaranthus palmeri resistance to PPO‐inhibitor herbicides is widespread in the US Mid‐south. Highly resistant populations are associated with multiple target‐site mutations within the population. Some resistant plants harbor double mutations. G399A is the most prone to co‐occur with other ppo2 mutations in the same allele. © 2020 Society of Chemical Industry